Reduction of Opiate Withdrawal Symptoms With Use of Clonidine in a County Jail. (January 2015) - Fresquez-Chavez, Kathy R.; Fogger, Susanne
Increasingly, addicted inmates admitted to jail in New Mexico are in the process of opiate withdrawal. While the standard for opiate detoxification is a narcotic taper, correctional policy restricts opiate use for safety reasons. An alternative for withdrawal is a supportive intervention with clonidine, a non-opiate. Could clonidine be beneficial for acute opiate withdrawal symptoms in this population? Fifty-five inmates (37 male and 18 female) volunteered to participate in assessing clonidine for the reduction of withdrawal symptoms. Symptoms were assessed with the Subjective Opiate Withdrawal Scale and treated with a standard clonidine protocol. Clonidine significantly decreased the mean scores at 1 and 4 hours after medication use. Clonidine for opiate withdrawal reduces symptoms when opiate-assisted detoxification is not available.